2011
DOI: 10.1111/j.1476-5381.2011.01228.x
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoid modulation of GABAA receptors

Abstract: There has been a resurgence of interest in synthetic and plant-derived flavonoids as modulators of g-amino butyric acid-A (GABAA) receptor function influencing inhibition mediated by the major inhibitory neurotransmitter GABA in the brain. Areas of interest include (i) flavonoids that show subtype selectivity in recombinant receptor studies in vitro consistent with their behavioural effects in vivo, (ii) flumazenil-insensitive modulation of GABAA receptor function by flavonoids, (iii) the ability of some flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
154
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 201 publications
(164 citation statements)
references
References 92 publications
(114 reference statements)
5
154
0
5
Order By: Relevance
“…Previous works have reported the anticonvulsant and sedative properties of flavonoids (Johnston, 2005;Yao et al, 2010;Hanrahan et al, 2011). Flavonoids, found to be present in the ethyl acetate fraction of methanol root bark extract of S. virosa, may therefore be responsible for the observed anticonvulsant and sleep promoting activities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous works have reported the anticonvulsant and sedative properties of flavonoids (Johnston, 2005;Yao et al, 2010;Hanrahan et al, 2011). Flavonoids, found to be present in the ethyl acetate fraction of methanol root bark extract of S. virosa, may therefore be responsible for the observed anticonvulsant and sleep promoting activities.…”
Section: Discussionmentioning
confidence: 99%
“…30 The present work showed the dose dependent anxiolytic effect as evidenced from the significant increase in the frequency and time spent in open arms by the animals treated with 50 and 100 mg/kg of EAFCF orally. Since, benzodiazepines are used for validating this animal model 30 and flavonoids are believed to modulate GABAergic system, 31 it is suggested that EAFCF, being rich in flavonoids, may produce its anxiolytic activity by acting on GABA A receptor mediated GABAergic system. To investigate the role of GABAergic system, flumazenil (GABA A receptor antagonist) was administered before the treatment of EAFCF and the results showed that the pretreatment of flumazenil blocked the anxiolytic effect of EAFCF in EPM.…”
Section: Discussionmentioning
confidence: 99%
“…Loeselia Mexicana, 32 Piper methysticum, 33 Euphorbia hirta, 34 and Cymbopogon citratus) have also been reported to mediate their anxiolytic activity through GABAergic system. 31,35 The open-field test is based on the rodents intrinsic behaviour to stay near the periphery of a novel environment (ie. thigmotaxis), which may provide the animal a sense of security.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lavonoids can inluence GABA A receptors via the classical benzodiazepine-binding site, as well as independently of the classical benzodiazepine-binding site [3,16]. Many lavonoids elicit biphasic responses, enhancing GABA actions at low concentrations and inhibiting at high concentrations.…”
Section: Flavonoids and Benzodiazepinesmentioning
confidence: 99%